The Effect of Competence on Employees ’Performance with Physical and Leadership Work Environment as Moderating Variables on CV. Bali Bhuana Garment Denpasar - Pradnyana, Made Agus Wija; Agung, Anak Agung Putu; Landra, Nengah (RA Journal of Applied Research, 2018)
The aim of this study was to determine and examine the influence of competency on employee performance on the CV. Bali Bhuana Garment Denpasar, To find out and test whether the physical work environment can moderate the relationship between competence on employee performance on the CV. Bali Bhuana Garment Denpasar, To find out and test whether leadership can moderate the relationship between competence on employee performance on CV. Bali Bhuana Garment Denpasar. This research is a quantitative research using primary data obtained from questionnaires and measured using a Likert scale. Based on data taken from CV. Bali Bhuana Garment Denpasar where employees number 52 people, which is less than 100, then taken entirely so that the research is a saturated sample population research. Data analysis techniques used in this study are Moderated Regression Analysis (MRA) based using SPSS19 program assistance. Based on the results of research and discussion related to the influence of competence on employee performance with the physical and leadership work environment as a moderating variable on CV. Bali Bhuana Garment Denpasar, the conclusion can be drawn as follows: (1) competence has a positive and significant effect on employee performance. (2) the physical work environment can moderate the relationship between competencies and employee performance. (3) leadership can moderate the relationship of competence with employee performance.